Leadership, trust in management and acceptance of change in Hong Kong's Civil Service Bureau. Issue 5 (10th July 2018) - Cai, Wen Juan; Loon, Mark; Wong, Peter Hoi Kin
Abstract : Purpose: The purpose of this paper is to examine whether trust in management mediates the relationships between two types of leadership (transactional and transformational) and acceptance of change in the Hong Kong public sector. Design/methodology/approach: Data from 68 civil servants in the Hong Kong SAR Government were used in the partial least squares analysis. Findings: The findings from civil servants show that although trust in management mediates the relationship between both types of leadership and acceptance of change, transformational leadership is more effective in increasing both trust and acceptance of change. Research limitations/implications: The strong support for the mediation hypotheses highlights the need for leaders to be trusted by their followers if followers are to accept and support the change process. Trust in management is what ultimately reduces resistance to change. Practical implications: The findings from this study have demonstrated that one strategy available to leaders in the Hong Kong public sector is to concentrate on developing perceptions of trustworthiness by utilising both transactional leadership and transformational leadership but especially transformational leadership. Originality/value: This paper provides a unique and nuanced view of leadership and trust, and their effect on the acceptance of change in Hong Kong's civil service bureau that operates in a turbulent environment. Public sector organisations in Hong Kong are unique in that they contend with pressures from Hong Kong nationals and also with pressures from the Government of Mainland China.